Análise da lei de regularização fundiária municipal e sua aplicação na cidade de Uberlândia – MG, sob o enfoque do direito à moradia - Bernardes, Iris Cristina Fernandes Vieira (2024)
To guarantee the right to housing, it is necessary to commit to the practical application of the legal instruments provided for in Federal Law No. 13,465/2017, responsible for regulating rural and urban land regularization. This research intended to study the limitations that municipal legislation imposes on the land regularization of existing consolidated centers in the city of Uberlândia – MG, by establishing new limiting criteria that do not comply with the provisions of the Federal Law, and are out of step with the fundamental right to housing. and property, as they are distinct rights. With the purpose of illustrating the present research problem, it was verified whether the determination of Municipal Laws nº 670/2019 and nº 671/2019 in the sense that it is only possible to regularize informal nuclei proven to exist until December 22, 2016, brings limitations to the applicability of Federal Law No. 13,465/2017 and consequently to the right to housing, since the Federal Law only restricts the use of the land legitimization instrument after this time frame. The research hypothesis was that the Municipality of Uberlândia, both in Municipal Complementary Law nº 670/2019, Municipal Complementary Law nº 671/2019 and Municipal Complementary Law nº 738/2022, would, under the pretext of preventing the occurrence of disorderly land subdivision and invasions of public and private property, mitigating the responsibility of the Municipal Executive Branch for inspection, obstructing the land regularization of occupations consolidated after the time frame established in the legislation, to the detriment of the right to housing, unduly restricting the application of federal legislation. The general objective of this research was to investigate whether the Municipality of Uberlândia, both in Municipal Complementary Law No. 670/2019, Municipal Complementary Law No. 671/2019 and Municipal Complementary Law No. 738/2022, is unduly restricting the general regulations provided for in Federal Law 13,465/2017, limiting the constitutionally foreseen right to housing, mitigating the responsibility of the Municipal Executive Branch for inspection, obstructing the land regularization of consolidated occupations, to the detriment of the right to housing. The research was divided into three parts, so that the first chapter addressed the right to the city and the right to housing, as well as their relationship with the right to property and the social function of property; the second chapter addressed specific aspects of urban land regularization; and the third chapter will analyze the municipal land regularization law of Uberlândia – MG, with numerical data that allow the achievement of the objectives of this work, under the focus of the right to housing, going through the City Statute, the Constitution and the legislation itself municipal. In the end, it was concluded that the time frame of December 22, 2016 was significant, resulting in the rejection of 36 of the 124 projects presented – which means a percentage of almost thirty percent of the projects submitted, confirming the research hypothesis. The deductive method of approach was adopted to, from a methodological point of view, delimit the structure of the research into chapters.